PAKET WISATA PT. PDA TIGI MA’AYA TOUR & TRAVEL DI PEKANBARU - Nadia Lesmona; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted at PT. PDA Tigi Ma’aya Tour & Travel Pekanbaru. As for the background of this research is lack of promotion wich do PT. PDA Tigi Ma’aya Tour & Travel for promotion tour package wich applying Islamic values. The purpose this research is for knowing execution of promotion tour package wich applying Islamic values to consumen. This research uses theory that discusses Lupiyoadi and Hamdani which to explain phenomena promotion was happened in the company. This research is using qualitative methods, while the technique of data collection using deep interviews with guest speaker. Furthermore, the data in the form of data qualitative and quantitative data were analyzed with descriptive technical data analysis.Results of this research showed many still a society not yet know about tour package wich using Islamic concept in PT. PDA Tigi Ma’aya Tour & Travel. PT. PDA Tigi Ma’aya Tour & Travel must more improving for promoting tour package to society with promotion mix methods.Key words : Promotion, Tour Package, Islamic Values